Epidemiological Study of Hydatid Cyst of Echinococcus Granulosus Isolated from Sheep and Goats in Duhok Province, Kurdistan Region of Iraq. - SARGALI, ARSHAD MOHAMMAD ABDULLAH; MERO, WIJDAN MOHAMMAD SALIH (Science Journal of University of Zakho, 2013)
This study included an epidemiological study on hydatidosis which included the examination of 63483 sheep and 13960 goats slaughtered at Duhok Abattoir during the period from Nov.2008 to Oct. 2009. It has been found that 12.3% of sheep and 5.17% of goats were infected with HCs. Among sheep 56.10% of HC were found in the lungs, 36.25% in the liver and 7.66% in both liver and lungs. Among goats 67.31% of the HCs found in the lungs, 25.5% in liver and 7.20% in both liver and lungs. The highest % of sheep occurred in summer (14.74%) and the lowest (9.9%) during spring, whereas, the highest % in goats (11.24%) was during spring and the lowest (2.47%) during winter.
Keywords: The